Brains of rhesus monkeys display Aβ deposits and glial pathology while lacking Aβ dimers and other Alzheimer's pathologies. Issue 4 (4th June 2019) - Zhang, Jing; Chen, Baian; Lu, Jing; Wu, Yi; Wang, Shubo; Yao, Zitong; Zhu, Liming; Qiao, Yanhua; Sun, Quan; Qin, Wei; Zhao, Qiao; Jia, Jianping; et al.
Abstract: Cerebral amyloid beta (Aβ) deposits are the main early pathology of Alzheimer's disease (AD). However, abundant Aβ deposits also occur spontaneously in the brains of many healthy people who are free of AD with advancing aging. A crucial unanswered question in AD prevention is why AD does not develop in some elderly people, despite the presence of Aβ deposits. The answer may lie in the composition of Aβ oligomer isoforms in the Aβ deposits of healthy brains, which are different from AD brains. However, which Aβ oligomer triggers the transformation from aging to AD pathogenesis is still under debate. Some researchers insist that the Aβ 12‐mer causes AD pathology, while others suggest that the Aβ dimer is the crucial molecule in AD pathology. Aged rhesus monkeys spontaneously develop Aβ deposits in the brain with striking similarities to those of aged humans. Thus, rhesus monkeys are an ideal natural model to study the composition of Aβ oligomer isoforms and their downstream effects on AD pathology. In this study, we found that Aβ deposits in aged monkey brains included 3‐mer, 5‐mer, 9‐mer, 10‐mer, and 12‐mer oligomers, but not 2‐mer oligomers. The Aβ deposits, which were devoid of Aβ dimers, induced glial pathology (microgliosis, abnormal microglia morphology, and astrocytosis), but not the subsequent downstream pathologies of AD, including Tau pathology, neurodegeneration, and synapse loss. Our results indicate that the Aβ dimer plays an important role in AD pathogenesis. Thus, targeting the Aβ dimer is a promising strategy for preventing AD. Abstract : Aβ deposits in aged monkey brains included 3‐mer, 5‐mer, 9‐mer, 10‐mer, and 12‐mer oligomers, but not 2‐mer oligomers. The Aβ deposits, which were devoid of Aβ 2‐mer oligomers, induced glial pathology (microgliosis, abnormal microglia morphology, and astrocytosis), but not the subsequent downstream pathologies of AD, including Tau pathology, neurodegeneration, and synapse loss.